Litíase intrahepática primária. Relato de caso e revisão da literatura. - Pereira, E.; Kannebley, J.; Carvalho, M.; Mendes, R.; Marques, M.; Franco, M. (My University, 1994)
Primary intrahepatic lithiasis is an entity defined by intrahepatic stones exclusively located in the IH ducts above the emergence of the common bile duct. The disease is classified in two types: Eastern type (stones formed primarily in intrahepatic ducts; frequent in Japan) and Western type (stones formed in the extrahepatic bile system, usually in gallbladder, which migrate up to the intra-hepatic ducts). The mechanisms of lithogenesis in the entity are as yet not fully understood; multiple factors seem to operate synergistically: anatomical changes of the intrahepatic ducts, metabolic disorders, infections, idiopathic alteration. All these factors may facilitate biliary stasis leading ultimately to stone formation. We report on a case of and review the literature on primary intrahepatic lithiasis, which is a rare occurrence in the West and a disease of difficult surgical approach and high mortality.
Primary intrahepatic lithiasis: report of a case and review of the literature
Keywords: adult; case report; cholelithiasis; female; human; intrahepatic bile duct; pathology; review; Adult; Bile Ducts, Intrahepatic; Case Report; Cholelithiasis; English Abstract; Female; Human